1991
DOI: 10.1159/000261338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Surface-Active Cation on Fluoride/Enamel Interactions in vitro

Abstract: After in vitro treatments of bovine enamel with NaF/Zonyl FSC and NH4F in-depth profiles of the chemical composition of the outermost zone of surface enamel were obtained with electron spectroscopy. The most important finding of the study was that after the treatments with nearly neutral as well as slightly acidic solutions of NH4F the ammonium cation was found on the enamel surfaces. Similarly a Zonyl FSC layer was detected on the enamel surfaces after the NaF/Zonyl FSC treatment, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…On the basis of photoemission studies on bovine or human enamel, it was hitherto believed that fluoridation affects the enamel up to microscopic depths, i.e., depending on parameters such as application time, pH value, temperature, and F – concentration, the thickness of FAp layers ranges from several tens of nanometers to several microns. However, in 2010, experiments on synthetic HAp samples, as representing a macroscopic counterpart of a single grain from enamel, revealed that the thickness of the FAp layer is just in the range of about 10 nm . This experimental finding is supported by former molecular dynamic simulations predicting that “the fluoride is not expected to penetrate deeply into the apatite material” .…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of photoemission studies on bovine or human enamel, it was hitherto believed that fluoridation affects the enamel up to microscopic depths, i.e., depending on parameters such as application time, pH value, temperature, and F – concentration, the thickness of FAp layers ranges from several tens of nanometers to several microns. However, in 2010, experiments on synthetic HAp samples, as representing a macroscopic counterpart of a single grain from enamel, revealed that the thickness of the FAp layer is just in the range of about 10 nm . This experimental finding is supported by former molecular dynamic simulations predicting that “the fluoride is not expected to penetrate deeply into the apatite material” .…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, for example, the economical loss caused by caries increased from 6.4 billion euros in 2002 to 7.5 billion euros in 2004 . Data from clinical investigations clearly demonstrate the cariostatic effect of fluoride compounds in various forms of applications. Although numerous experimental studies have been performed up to now, no model comprehensively describes the reaction mechanisms of fluoride with enamel.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with Ar ion etching, the surface sensitivity of XPS allows investigating the chemistry of the surface of the sample layer-by-layer with a depth resolution in the range of 1 nm. So far, literature reports on a large variety of such investigations, but the results of these studies are often contradictory, and therefore, there is still no consistent picture concerning the mechanism of fluoridation. In contrast, it seems that each new experiment provides new results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphoteric surfac tants have had little application in this area. Various surfac tants have also been shown to interact with enamel or to af fect enamel fluoride interactions Gron and Caslavska, 1983;Borggreven ct al., 1989;Caslavska and Duschner, 1991;Fox et al. 1992].…”
Section: Introductionmentioning
confidence: 99%